UTILIZATION OF PRODUCT MARKETING STRATEGIES FOR BUSINESS SUCCESS BY OWNERS OF SME IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
This study ascertained extent of utilization of product marketing strategies for business success by owners of SMEs in Anambra State. This necessitated by the need to ensure that SMEs make their own products unique and distinct in the marketplace that will enhance them for future competitiveness. Two research questions guided the study and two null hypotheses were tested. Descriptive survey research design was adopted for the study. The population comprised all 1,813 Registered SMEs owners practicing in Anambra State. The sample of 544 was used through a stratified random sampling technique. The instrument for data collection was a 20-item questionnaire. The instrument was validated by three experts. Cronbach Alpha was used to determine the reliability of the items instrument and obtained an overall coefficient value of 0.87. Mean and standard deviation were used to answer the research questions, while ANOVA was used to test the null hypotheses at 0.05 level of significance. The findings of the study revealed that product branding strategies were greatly utilized, while the positioning marketing strategies were moderately utilized. Also, owners of SMEs differ significantly in their mean ratings on the extent they utilized product branding and positioning marketing strategies based on years of experience. The study concluded that product branding strategies are used more than the positioning marketing strategies by SMEs in a highly competitive market such as Anambra State. It was therefore recommended among others that, owners of SMEs in Anambra State should utilize product packaging and positioning strategies because it will enable them have great influence on consumer’s perception of product as an incentive to consumers to choose their product.
Keywords: Marketing strategies; product marketing strategies; owners of SMEs